2012
DOI: 10.1007/s10660-012-9089-5
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on consumer first purchase intention in online shopping: integrating initial trust and TAM

Abstract: To understand the first purchase mechanism in online shopping, this study established an integrated model of initial trust and TAM. According to the analysis results, initial trust beliefs were significantly influenced by initial trust bases such as company reputation, structural assurance, and trusting stance, and initial trust beliefs indirectly influenced the first purchase intention through consumer attitude. In TAM constructs, only perceived usefulness directly influenced the usage attitude of online shop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
129
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(147 citation statements)
references
References 86 publications
(165 reference statements)
8
129
1
9
Order By: Relevance
“…However, comparisons between innovation adoption theories show that the TAM appears to have advantages over the TPB and the DOI because it is a simpler model that is easier to apply and more efficient in predicting and explaining an individual's adoption intentions and actual behavior. Many studies that investigate m-payment service adoption have selected the TAM over other theories because it allows a causal validation of variables (M. Chen & Teng, 2013;J. B. Kim, 2012;Phonthanukitithaworn et al, 2015Phonthanukitithaworn et al, , 2016, an exploration of the adoption of m-payment services (Goeke & Pousttchi, 2010;Keramati et al, 2012;C.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, comparisons between innovation adoption theories show that the TAM appears to have advantages over the TPB and the DOI because it is a simpler model that is easier to apply and more efficient in predicting and explaining an individual's adoption intentions and actual behavior. Many studies that investigate m-payment service adoption have selected the TAM over other theories because it allows a causal validation of variables (M. Chen & Teng, 2013;J. B. Kim, 2012;Phonthanukitithaworn et al, 2015Phonthanukitithaworn et al, , 2016, an exploration of the adoption of m-payment services (Goeke & Pousttchi, 2010;Keramati et al, 2012;C.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…According to the Simon-Kucher Partners' (2015) survey, bank reputation is the second most important criterion considered by French consumers. Other studies have shown that bank reputation enhances consumers' initial trust in the internet and mobile banking (Dimitriadis & Kyrezis, 2008;Kim, 2012;Montazemi & Qahri-Saremi, 2015, Yousafzai et al, 2009. It has been shown that trust strongly affects the French consumers' decision to use internet banking and their loyalty toward it (Sahut et al, 2011;Sanchez & Gallie, 2010).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Por otra parte, de acuerdo con Kim (2012), el ciclo de vida de la confianza está marcado por la primera compra que realiza el consumidor. ¿Deberíamos entonces suponer que la confianza inicial conlleva a la compra?…”
Section: Confianzaunclassified